Students' Perception on Using YouTube As A Tool in Learning Speaking English - Jailani, Abdul Qodir; Wahab, Abdul Aziz; Ferdiyanto, Feri (International Journal of English Education and Linguistics (IJoEEL), 2024)
In language learning, the learners need to acquire the knowledge of some skills such as speaking, writing, listening, and reading. Among the four skills, speaking is said to be a very important skill. The purpose of this study is to find out students' perception on the use of YouTube in learning English speaking skill. More specifically, this study is directed to explore the benefits of using YouTube channels in learning English. The researchers used qualitative method. thus, the researchers used interviews to collect the data. Researchers chose interviews to find out the perceptions of students and also wanted to find out deeper information from participants. The researchers asked several questions related to research questions. The Participant of this research is the student of English education department and there were three students from sixth semester of English education department. The researchers used that class because the students used YouTube as a medium in learning speaking English the finding show that digital media is very important in learning English especially in using YouTube. student have their perceptions about using YouTube in learning speaking English. the researchers found many Benefits of using YouTube as A tool in learning speaking English. based on the interview data, the researcher interview Three students. They are students said that YouTube is very useful and has many benefits in learning English, especially in learning to speak English. However, researchers found little negative impact from using YouTube media as a tool in learning to speak English.